Pendidikan kesehatan dengan media pop-up meningkatkan pengetahuan gizi seimbang siswa sekolah dasar - Permatasari, Firlya Sanafa; Rahmawati, Agustina; Isnaeni, Yuli (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Elementary school children are in a growth and development phase and require balanced nutrition. Lack of knowledge can lead to nutritional problems such as undernutrition and overnutrition. Health education using engaging media can improve children's knowledge of balanced nutrition. Purpose: To determine the effect of health education using the